Unique norbornene based triazole molecule for selective Fe(ii) sensing1. Issue 91 (9th October 2015) - Bhattacharya, Sourav; Shunmugam, Raja
<x xml:space="preserve">Abstract</x> A triazole functionalized norbornene monomer (NFTZ) and its corresponding homopolymer (NFTZH) are synthesized for selective Fe(ii) sensing.